The Great Patriotic War - Turning Point of the Second World War - สุวังบุตร, สัญชัย (Journal of the Faculty of Arts, Silpakorn University, 2020)
When Nazi Germany invaded the Soviet Union on June 21, 1941, Adolf Hitler - the Nazi leader - was determined to conqure the Soviet Union and force a surrender within 2 months. German armies using Blitzkrieg tactics were victorious on all fronts. However, Stalin – the soviet leader - ordered his troops not to surrender or retreat which prevented the Soviet from falling back. Pravda the communist newspaper, reported the news of the war in a long article entitled “The Great Patriotic War of the Soviet People” in order to encourage the population to defend the Soviet fatherland and to expel the invaders. Thus, the Soviet named the War from 22 June 1941 to 9 May 1945 between the Soviet Union and Germany as the Great Patriotic War. The turning points of the war were the Battle of Stalingrad and the Battle of Kursk in 1943 because the german armies were defeated and never again won a major battle on the Eastern front. Soviet forces began to liberate their nation and continued to push the Germans back for the next two years. The Soviet captured Berlin in April 1945. The war ended in complete defeat for Nazi Germany. In the Soviet Union, the war ended on May 9, 1945 when Germany surrendered. The day has become a national holiday – Victory Day.